2019
DOI: 10.5380/dma.v52i0.59993
|View full text |Cite
|
Sign up to set email alerts
|

A sustentabilidade em meios de hospedagem: enfoque na materialidade dos serviços

Abstract: Ao mesmo tempo em que o turismo é reconhecido como atividade causadora de danos ao meio ambiente, a imaterialidade permanece aceita como característica dos serviços em geral, e, portanto, também dos serviços turísticos. O artigo tem como objetivo discutir, à luz de novas abordagens que questionam o entendimento convencional dos serviços, a materialidade dos serviços de hospedagem. Para alcance desse objetivo, é realizada uma pesquisa exploratória. Os dados foram coletados a partir de revisão da literatura sobr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 72 publications
0
3
0
2
Order By: Relevance
“…The service activity requires inputs (resources) and consequently generates outputs (releases) that can cause adverse effects on the environment. Therefore, the inputs and outputs in the product life cycle (goods and services) clarify the relevant environmental aspects for the systematic consideration of environmental issues and understanding how the product interacts with the environment [9].…”
Section: Environmental Aspects Of Lodging Facilities In Mossoró-rnmentioning
confidence: 99%
See 2 more Smart Citations
“…The service activity requires inputs (resources) and consequently generates outputs (releases) that can cause adverse effects on the environment. Therefore, the inputs and outputs in the product life cycle (goods and services) clarify the relevant environmental aspects for the systematic consideration of environmental issues and understanding how the product interacts with the environment [9].…”
Section: Environmental Aspects Of Lodging Facilities In Mossoró-rnmentioning
confidence: 99%
“…In lodging facilities, the provision of services requires the following inputs: water, energy, food and beverages, cleaning products, personal hygiene products, chemicals, fossil fuels, and other products. It also generates outputs: organic and inorganic waste, effluents and atmospheric emissions, noise, odors [9] In this context, investigating the lodging facilities in Mossoró-RN revealed that water is an indispensable element, with consumption directly related to the size of the establishments. The data obtained also revealed that despite the dependence on public supply, there are visible strategies for supplementary water supply in case of scarcity.…”
Section: Environmental Aspects Of Lodging Facilities In Mossoró-rnmentioning
confidence: 99%
See 1 more Smart Citation
“…O setor de turismo é formado por empresas provedoras de serviços, como os meios de hospedagem, agências de viagens, empresas de passeio dentre outros (Sarquis, Pizzinatto, Giuliani & Pontes, 2015;Volpi & Paulino, 2019), exercendo assim um grande papel no desenvolvimento global se correlacionando com o crescimento da economia (Khan, Hassan, Fahad & Naushad, 2020). Fatores como: cultura, paz, segurança, infraestrutura, os vistos, atitude das pessoas, educação, nível de renda, preço das commodities, idiomas, hotéis, viagens e os destinos turísticos de cada país influenciam na economia destes (Khan, Hassan, Fahad & Naushad, 2020).…”
Section: Covid-19 E Turismounclassified
“…De maneira geral, todos os três respondentes concordam que todo o setor do turismo foi afetado de maneira drástica, em decorrência da pandemia (Coelho & Mayer, 2020), pois o setor do turismo não só da região, mas de localidades turísticas, em especial da Rota das Emoções que é o objeto de estudo, são interligados, desde das companhias de viagem, operadoras, receptivos (empresas de passeio), hotéis (Vieira, Hoffmann & Alberton, 2018;Volpi & Paulino, 2019), todos foram impactados de alguma maneira de acordo com os entrevistas, uns mais, outros menos, mas de maneira macro todos por serem conectados estão sofrendo perdas por causa do COVID-19 (Romão, 2020;Sayfullaev, 2020).…”
Section: Quadro 10 -Empresas Do Turismo Com Maior Desgaste Com a Pandemia E Pós Covid-19unclassified